Gempa Perekat: The movement to process garbage becomes an educational game tool for early childhood through self-help groups for family welfare development - Mizam Ari Kurniyanti; Ahmad Guntur Alfianto; Miftakhul Ulfa; Ari Dwi Sulaksono (Journal of Community Empowerment for Health, 2023)
Garbage is a major problem in urban areas. One of the efforts that can be made against the waste problem is reprocessing it into useful materials. The Family Welfare Development Group (PKK) is a community action coaching group that demonstrates ways that people can turn waste into media material for educational games for PAUD students through self-help groups. This community service project and research aimed to empower and assist PKK activist groups in optimizing waste as an educational game tool for young children. The mixed-methods research followed quantitative and qualitative approaches. The quantitative data were in the form of demographic data, knowledge, and skills. Meanwhile, the qualitative data were collected from structured interviews and focus group discussions (FGDs) with a grid of questions about waste, the efforts that have been made, and the benefits of recycling the waste as an educational game tool. The measuring tool used was a questionnaire about waste knowledge and a waste processing checklist sheet. The research was conducted in June-August 2019 among 25 PKK groups at RW 02 of Merjosari subdistrict, Lowokwaru district, Malang City, because this location clearly shows a waste problem, and the community can manage it with facilities that can be readily utilized. ThisGempa Perekatactivity consisted of health education, FGDs, and forming self-help groups. The results of this activity indicated that the respondents’ knowledge increased after receiving health education about waste management (0.000). The results showed an average value of 73 with description skills in processing waste into a good educational game tool. Respondents stated that waste was previously disposed of in plastic bags or burned. Furthermore, they hoped that there would be waste management approaches that could be useful for PAUD students by processing waste into educational games. This activity concluded that the Gempa Perekatprogram is a feasible form of intervention in dealing with garbage in the city by empowering the PKK as a self-help group in making educational game tools for PAUD students from waste.